The Nomen Juris in Relation to the Grounds for the Invalidity of a Legal Transaction - León Barandiarán, José (1974)
This article explores in detail the relationship between the nomen juris and the grounds for invalidity in legal transactions, highlighting the importance of precision and detail in legal terminology. In relation to legal transactions, the author points out that some of them may be ineffective due to deficiencies in their conclusion, lack of necessary requirements, incapacity of the parties, having a physically impossible object, among other congenital legal defects or supervening causes. Along these lines, he develops different terms, such as nullity, annulment, impugnation, rescission, revocation, dissolution and resolution. Taking into consideration the different denominations that exist, the author concludes by emphasizing the importance of precision in legal terminology in order to accurately reflect the legal concepts to avoid confusion and tensions between the field of law and language.